Perubahan Populasi Mikroroganisme Pelarut Fosfat pada Lahan Sawah dengan Sistem Pertanian Intensif menjadi Sistem Pertanian Organik Berkelanjutan - Dermiyati Dermiyati; Jeni Antari; Sri Yusnaini; Sutopo Ghani Nugroho (UNIVERSITY OF LAMPUNG, 2009)
Changes of Phosphate Solubilizing Bacteria Population on Paddy Field with Intensive Farming became Sustainable Organic Farming System (Dermiyati, J. Antari, S. Yusnaini, and S.G. Nugroho): The research aimed to study the change of population of phosphate solubilizing microorganisms according to the application time of bokashi which were applied continously on organic paddy rice fields since years of 2000 up to 2006. The research was conducted in a Randomized Completely Block Design in four replicates. The treatments were without bokashi (control; with intensively application of NPK fertilizers), bokashi application for 3 planting seasons (12 t ha-1), bokashi application for 4 planting seasons (16 t ha-1), bokashi application for 7 planting seasons (28 t ha-1), and bokashi application for 9 planting seasons (36 t ha-1). The results showed that the population of phosphate solubilizing microorganisms were not affected by continously applied of bokashi and did not have correlations to organic carbon, total nitrogen, ratio C/N, soil pH, and soil water content. However, the phosphate solubilizing microorganisms had played a role in the availability of the soil available-P which were shown by increasing of paddy yields year by year, although the contribution of soil phosphorus from bokashi is a relatively low. Yet, the bokashi application on the organic paddy fields did not increase the soil availble-P because most of the P which was absorbed by the plants coming from residual P fertilizers either from bokashi or SP-36 which were intensevely given before.